Persepsi Pengunjung Tentang Daya Tarik Wisata Kincia Cucu Antan Kari Di Kabupaten Agam - Sri Mulyani; Nidia Wulansari (Jurnal Manajemen Pariwisata dan Perhotelan, 2023)
This research was motivated by complaints from visitors on social media about the attractions of the Kincia Cucu Antan Kari tourist attraction in Agam Regency. This research aims to determine visitors' perceptions of the Kincia Cucu Antan Kari tourist attraction in Agam Regency as seen from 3 indicators, namely: Cognitive, affective and conative. The population of this study was 461 visitors who were visiting and who had visited the Kincia Cucu Antan Kari tourist attraction, from this total population there were 215 respondents. The data collection technique uses a questionnaire (questionnaire) with a Likert scale which has been tested for validity and reliability. The method used in this research is quantitative descriptive. Testing the analysis using data tabulation and measuring the level of respondent achievement (TCR) with the help of SPSS version 23.00. Based on the research results, it was found that visitors' perceptions of the Kincia Cucu Antan Kari tourist attraction in Agam Regency were categorized as quite good. Meanwhile, looking at each of the indicators, cognitive is in the quite good category, affective is in the quite good category and conative is in the quite good category. So it can be concluded that the overall perception of attractiveness at the Kincia Cucu Antan Kari tourist attraction in Agam Regency is quite good so it needs to be optimized further.